Relationship Between Time in Range, Glycemic Variability, HbA1c, and Complications in Adults With Type 1 Diabetes Mellitus - El Malahi, Anass; Van Elsen, Michiel; Charleer, Sara; Dirinck, Eveline; Ledeganck, Kristien; Keymeulen, Bart; Crenier, Laurent; Radermecker, Régis; Taes, Youri; Vercammen, Chris; Nobels, Frank; Mathieu, Chantal; et al. (The journal of clinical endocrinology and metabolism, 2022)
Abstract Purpose Real-time continuous glucose monitoring (RT-CGM) provides information on glycemic variability (GV), time in range (TIR), and guidance to avoid hypoglycemia, thereby complimenting HbA1c for diabetes management. We investigated whether GV and TIR were independently associated with chronic and acute diabetes complications. Methods Between September 2014 and January 2017, 515 subjects with type 1 diabetes using sensor-augmented pump therapy were followed for 24 months. The link between baseline HbA1c and CGM-derived glucometrics (TIR [70-180 mg/dL], coefficient of variation [CV], and SD) obtained from the first 2 weeks of RT-CGM use and the presence of complications was investigated. Complications were defined as: composite microvascular complications (presence of neuropathy, retinopathy, or nephropathy), macrovascular complications, and hospitalization for hypoglycemia and/or ketoacidosis. Results Individuals with microvascular complications were older (P < 0.001), had a longer diabetes duration (P < 0.001), a higher HbA1c (7.8 ± 0.9 vs 7.5 ± 0.9%, P < 0.001), and spent less time in range (60.4 ± 12.2 vs 63.9 ± 13.8%, P = 0.022) compared with those without microvascular complication. Diabetes duration (odds ratio [OR] = 1.12 [1.09-1.15], P < 0.001) and TIR (OR = 0.97 [0.95-0.99], P = 0.005) were independent risk factors for composite microvascular complications, whereas SD and CV were not. Age (OR = 1.08 [1.03-1.14], P = 0.003) and HbA1c (OR = 1.80 [1.02-3.14], P = 0.044) were risk factors for macrovascular complications. TIR (OR = 0.97 [0.95-0.99], P = 0.021) was the only independent risk factor for hospitalizations for hypoglycemia or ketoacidosis. Conclusions Lower TIR was associated with the presence of composite microvascular complications and with hospitalization for hypoglycemia or ketoacidosis. TIR, SD, and CV were not associated with macrovascular complications.